PORITES SAMPLE PREPARATION FOR Sr/Ca ANALYSIS. - Fadhilah Maryadi Putra; Oktiyas Muzaky Luthfi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
Climate change has affected to all ecosystem around the world, include to marine ecosystem. The effect of climate change is increasing of the sea level temperature, and affected to coral reef on generally. Coral animal are very sensitive to the temperature change,and will influence their skeleton growth. Skeleton at corals can tell us how climate change affected from century ago, trough the reconstruction process. Chemical substances in corals, which strontium (Sr) and calcium (Ca), can show us the variation of that substances inversely with sea level temperature. Porites coral usually used for this reconstruction. To analys the substances, researcher use a tool called ICP-EOS, a tool that measures the intensity of energy/radiation on a substances that changes atom. The activities carried out in Center of Isotop Aplication and Radiation, National Nuclear Energy Agency (PAIR-BATAN). The aim of this study was to find out the method for sample preparation before analys the substances of Sr and Ca.